2022
DOI: 10.3389/fpsyg.2022.929380
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory and Anticipated Emotions in Regular and Non-regular Exercisers – A Qualitative Study

Abstract: Future-oriented emotions could influence our decisions in everyday life and help understand why some individuals are physically active whilst others are not. Current literature distinguishes between two future-oriented emotion constructs: anticipatory and anticipated emotions. While anticipatory emotions are currently experienced emotions about a future event, anticipated emotions refer to the emotions that a person is expected to experience when confronted with a future event. The main aims of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…Anticipated Forecasted in relation to perceived outcomes of a given behavior; not experienced during decision-making; may or may not be experienced after decision-making (Loewenstein and Lerner, 2003;Mankad, 2012;Feil et al, 2022) Individual predicts they will experience regret in the event they lose money after choosing to gamble ➔ anticipated regret deters gambling (Schlösser et al, 2013) Immediate Experienced during decision-making; often accompanied by changes in physiological state (Loewenstein, 2000;Schlösser et al, 2013) Individual experiences excitement when presented with gambling opportunity ➔ excitement incentivizes gambling (Schlösser et al, 2013) Anticipatory Subcategory of immediate emotion; experienced during decision-making as a result of contemplating a given behavior (Loewenstein and Lerner, 2003;Mankad, 2012;Feil et al, 2022) Anxiety in response to thoughts of investing ➔ heightens perceived riskiness of investment option ➔ potential investor warded off (Loewenstein and Lerner, 2003) Incidental Subcategory of immediate emotion; experienced during decision-making as a result of extraneous factors (Loewenstein and Lerner, 2003 Like other behavior change models, TPB comes with theoretical limitations, one of which is the intention-behavior gap. The intention-behavior gap refers to the discrepancy between an individual's predicted and actual behavior (Ajzen and Schmidt, 2020); plausible explanations for this phenomenon include the provisional nature of intentions and the presence of methodological drawbacks (Sutton, 1998;Yuriev et al, 2020).…”
Section: Category Description Example With Potential Behavioral Conse...mentioning
confidence: 99%
See 1 more Smart Citation
“…Anticipated Forecasted in relation to perceived outcomes of a given behavior; not experienced during decision-making; may or may not be experienced after decision-making (Loewenstein and Lerner, 2003;Mankad, 2012;Feil et al, 2022) Individual predicts they will experience regret in the event they lose money after choosing to gamble ➔ anticipated regret deters gambling (Schlösser et al, 2013) Immediate Experienced during decision-making; often accompanied by changes in physiological state (Loewenstein, 2000;Schlösser et al, 2013) Individual experiences excitement when presented with gambling opportunity ➔ excitement incentivizes gambling (Schlösser et al, 2013) Anticipatory Subcategory of immediate emotion; experienced during decision-making as a result of contemplating a given behavior (Loewenstein and Lerner, 2003;Mankad, 2012;Feil et al, 2022) Anxiety in response to thoughts of investing ➔ heightens perceived riskiness of investment option ➔ potential investor warded off (Loewenstein and Lerner, 2003) Incidental Subcategory of immediate emotion; experienced during decision-making as a result of extraneous factors (Loewenstein and Lerner, 2003 Like other behavior change models, TPB comes with theoretical limitations, one of which is the intention-behavior gap. The intention-behavior gap refers to the discrepancy between an individual's predicted and actual behavior (Ajzen and Schmidt, 2020); plausible explanations for this phenomenon include the provisional nature of intentions and the presence of methodological drawbacks (Sutton, 1998;Yuriev et al, 2020).…”
Section: Category Description Example With Potential Behavioral Conse...mentioning
confidence: 99%
“…Prior research paints immediate emotions as a strong contender. For instance, Feil et al 's (2022) investigation on the affective drivers of physical activity discovered that immediate emotions associated with participants' earlier fitness sessions (1) resurfaced when participants pondered a prospective opportunity to exercise and (2) correlated with the participants' overall exercise frequency (Feil et al, 2022). Kuwabara and Pillemer (2010) analogously observed that participants prompted to recall pleasant university experiences subsequently experienced positive immediate emotions while deciding whether to contribute to their alma mater; additionally, the more intense their positive immediate emotions were, the stronger their intentions and decisions to contribute (Kuwabara and Pillemer, 2010).…”
Section: Category Description Example With Potential Behavioral Conse...mentioning
confidence: 99%
“…reactions would be experienced before they decide or take action (Feil et al, 2022). The alternative consequences of the success or failure of an expected action serve as inputs to the evaluation process and emotional experience (Bagozzi et al, 1999).…”
Section: Anticipated Emotions In Purchasing Decisionsmentioning
confidence: 99%
“…The key process of anticipated emotions is about forward-looking counterfactual thinking processes ( Mandel et al, 2005 ). In this process, a consumer imagines the possible results and what emotional reactions would be experienced before they decide or take action ( Feil et al, 2022 ). The alternative consequences of the success or failure of an expected action serve as inputs to the evaluation process and emotional experience ( Bagozzi et al, 1999 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this conception, “automatic affective responses can preserve the lessons and information from previous emotional experiences” ( Baumeister et al, 2007 , p. 172). This previous affective experience contributes to the anticipation of an affective state of a future event and influences the decision about future behavior (see in the context of physical activity, Feil et al, 2022 ). As similar concept, in the circumplex model of affect, the mental structure of core affect can be reflected by the two dimensions valence (pleasure vs. displeasure) and activation (high vs. low arousal; Russell, 1980 , 2003 ).…”
Section: Introductionmentioning
confidence: 99%